Progress In Implementing The Framework For Enhanced Fund Engagement On Governance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
This paper provides an interim update on implementation of the 2018 Framework for Enhanced Fund Engagement on Governance. This update is in advance of a comprehensive formal review of the Framework scheduled for mid-2021.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; Political Economy